A COMPARISON OF AGGREGATION/BROADCAST METHODS AND MULTICOMPUTER ARCHITECTURES, AND AN EXAMINATION OF THE COMMUNICATION OVERHEAD ON THE IBM PSERIES 655 - Markowsky, Linda (International Journal of Computing, 2014)
First, using a simulator, a detailed comparison of the butterfly and direct aggregation/broadcast methods on both hypercube and fully connected multicomputers, both with and without simulation of congestion, is made. Second, the communication overhead an IBM pSeries 655 is examined.